Generalized fractional calculus to a subclass of analytic functions for operators on Hilbert space - Yong Chan Kim; Jae Ho Choi; Jin Seop Lee (International Journal of Mathematics and Mathematical Sciences)
In this paper, we investigate some generalized results of applications of fractional integral and derivative operators to a subclass of analytic functions for operators on Hilbert space.